Teaching Students’Understanding of Innovative Pedagogy - Naifeld, Edni; Simon, Eitan (European Scientific Journal, ESJ, 2017)
The education system, is responsible for the training of each new generation, and consequently adapts itself over the years to changes in the surrounding society. Technological changes, the information revolution and changes in work habits necessitate fundamental change in teaching methods, so that it can appropriately prepare future generations for modern reality. The Teaching and Education College in northern Israel offers programs to train “future teachers”, highlighting dynamic environments, the integration of technology in teaching and innovative pedagogy. A qualitative study used an open-ended questionnaire to investigate students’ perceptions of the concepts “innovative pedagogy” and “integration of technology in teaching” during their first practicum year in the education system. Findings showed that the young students find it difficult to conceptualize these concepts and describe them in a superficial and concrete manner. Mediation is needed, to connect college learning of these concepts with the students’ practical work in the field.